Nogle bemærkninger vedrørende en samlet udgave af Grundtvigs dagbøger - Albeck, Gustav (Grundtvig-studier, 1976)
Some Considerations on the Collected Edition of Grundtvigs Diaries by dr. Gustav Albeck, a lecture given at the Grundtvig Society’s A.G.M. in Århus on Dec. 2nd 1976 In connection with the impending publication of the complete edition of Grundtvig’s Diaries attention is called to a number of lesser-known and often misinterpreted notes from Grundtvig’s youth, including his falling briefly in love in Feb. 1805 with a formerly unknown lady of the manor, Gerhardine Hincheldey, who died a spinster in 1850. In the diaries we also find Grundtvig’s first poetry translation of a medieval Icelandic poem, a single stanza of the poem Lilja, depicting the penetration of light into the kingdom of death. Grundtvig has broadened the description into three 8-lined stanzas, published here for the first time. Unlike Hans Christian Andersen and Søren Kierkegaard, Grundtvig did not keep a meticulous diary, preferring to write down brief backward glances at his own life. But the diaries are nevertheless an indispensable part of his works.